Phenotypic Markers Reflecting the Status of Overstressed Tea Plants Subjected to Repeated Shade Cultivation - Yamashita, Hiroto; Tanaka, Yasuno; Umetsu, Keisuke; Morita, Sakurako; Ono, Yoshiki; Suzuki, Toshikazu; Takemoto, Tetsuyuki; Morita, Akio; Ikka, Takashi (Frontiers in Plant Science, 2020)
Shade cultivation is a traditional Japanese method of tea cultivation by which the shoot buds are shaded for several weeks. The technique is increasingly used for green tea production because the tea is of high quality (as indicated by umami and nutritional content) and commands high prices. However, given that shaded tea plants are grown under low-light stress, there are concerns about the damage to tea plants caused by repeated shade cultivation. To understand the basic physiological responses and accumulative changes in photosynthetic ability and metabolites of tea plants subject to repeated shading, we performed a pot experiment on immature tea plants grown in a growth chamber with repeated shading treatment. The results demonstrated that shade cultivation caused a decrease in nonstructural carbohydrate content and increase in leaf surface temperature, reflecting transpiration through the leaf stomata, as a result of reduction in photosynthetic ability. An increase in canopy temperature in the field in the mid-summer season was observed in overstressed tea plants subjected to repeated shading. Metabolome analysis identified a number of candidate biomarkers that were significantly changed in individuals affected by shade cultivation. These physiological changes may be an indicator of the stress status of tea plants grown under repeated shade cultivation.